2009
DOI: 10.4322/rbpv.01804001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of equine Piroplasmosis and its association with tick infestation in the State of São Paulo, Brazil

Abstract: Serum samples were collected from 582 horses from 40 stud farms in the State of São Paulo and tick (Acari: Ixodidae) infestations were evaluated on them. Serum samples were subjected to the complement fixation test (CFT) and a competitive inhibition ELISA (cELISA) for Babesia caballi and Theileria equi. Logistic regression analyses were performed to construct multivariate models that could explain the dependent variable (horses positive for B. caballi or T. equi) as a function of the independent variables (pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
3
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 30 publications
6
40
3
4
Order By: Relevance
“…Ambos, T. equi e B. caballi, têm sido relatados em outros estados do Brasil, como em algumas regiões de Goiás, Mato Grosso dos Sul, Minas Gerais e São Paulo (Battsetseg et al, 2002;Kerber, et al, 2009;Salvagni et al, 2010). Além disso, a maior frequência de T. equi observada no presente estudo, quando comparado a B. caballi, assemelha-se a resultados de outros autores (Heuchert et al, 1999;Kerber et al, 1999).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Ambos, T. equi e B. caballi, têm sido relatados em outros estados do Brasil, como em algumas regiões de Goiás, Mato Grosso dos Sul, Minas Gerais e São Paulo (Battsetseg et al, 2002;Kerber, et al, 2009;Salvagni et al, 2010). Além disso, a maior frequência de T. equi observada no presente estudo, quando comparado a B. caballi, assemelha-se a resultados de outros autores (Heuchert et al, 1999;Kerber et al, 1999).…”
Section: Discussionunclassified
“…Além disso, a maior frequência de T. equi observada no presente estudo, quando comparado a B. caballi, assemelha-se a resultados de outros autores (Heuchert et al, 1999;Kerber et al, 1999). Por outro lado, dados de soroprevalência para piroplasmose equina no estado de São Paulo demonstraram maior ocorrência da B. caballi, quando comparado a T. equi (Kerber et al, 2009). Nesse mesmo trabalho, Kerber et al (2009) Não houve reações positivas para N. risticii.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…However, Heuchert et al (1999) tested 752 serum samples from the state of São Paulo by IFAT and CFT and reported prevalence rates of 29.6 and 17.6%, respectively. More recently, Kerber et al (2009) reported an overall prevalence of 21.6% for T. equi by CFT and cELISA in horses of stud farms also in the State of São Paulo. The rate of equine piroplasmosis found in this study is significantly higher and is probably due to differences in the management of horses, which appears to be an important factor for the prevalence of T. equi infections, and, to a lesser extent, due to the number of serum samples examined.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported the association of tick infestation (KERBER et al, 2009), age (RIBEIRO et al, 1999;RÜEGG et al, 2007;KOUAM et al, 2010), breed system BOTTEON et al, 2002;MORETTI et al, 2010), horse farm activity, geographic area, season of the year and geldings (SHKAP et al, 1998;RÜEGG et al, 2007;KOUAM et al, 2010;MORETTI et al, 2010) with T. equi infection. However, other factors may be associated to infection because the epidemiological characteristics of disease may differ between regions.…”
Section: Introductionmentioning
confidence: 99%